DUS characterization of traditional varieties and advanced cultivars of rice using 29 essential characters - Akshay, M; Chandra, B Satish; Devi, K Rukmini; Hari, Y; Vamshi, P (ORYZA-An International Journal of Rice, 2022)
For the establishment of the distinctness, forty-four genotypes of rice were characterized at different stages of crop growth using 29 agro-morphological traits following Distinctiveness, Uniformity and Stability test (DUS) during rabi, 2020-21 at Regional Agricultural Research Station, Warangal. The rice genotypes under study recorded a wide range of variability for most of the essential traits studied. Out of 29 descriptors studied, two characteristics leaf auricles and leaf ligule shapewere found monomorphic, six were dimorphic, ten traitswere trimorphic, seven other characters resulted tetramorphic. The descriptors that registered maximum variation were decorticated grain: colour, decorticated grain: shape (in lateral view), panicle: attitude of branching, spikelet: colour of tip of lemma were found to be polymorphic in nature. This comprehensive characterization of rice genotypes is very important for rice breeding and will be beneficial for breeders, researchers and farmers from the stand point of selection and conservation of different landraces for further utilization in crop improvement programmes and also to seek protection under Protection of Plant Varieties and Farmers Rights Act.